002 Inhibition and Excitation in the Sexual Brain: An Useful Tool for the Prediction of Therapeutic Outcomes in Women with Sexual Dysfunction. (1st May 2022) - Maseroli, E.; Cipriani, S.; Stasi, V. Di; Scavello, I.; Alfaroli, C.; Maggi, M.; Vignozzi, L.
ABSTRACT: Introduction: The "Dual control model" of sexual response postulates that sexual desire and associated behaviors depend on the balance between excitation and inhibition. These aspects have not been evaluated in women with sexual dysfunction (FSD). Objective: To explore the psychosexual correlates of excitation and inhibition in women with FSD, according to their menopausal state. We also aimed at performing a pre-post analysis in a sub-sample of patients followed for 3-6 months, investigating the possible relationships between excitation and inhibition and the changes in questionnaires related to sexual function. Methods: In an observational, retrospective study, we recruited a consecutive series of 66 women consulting for FSD. Patients underwent a clinical evaluation, a structured interview and completed several self-administered questionnaires, including Sexual Inhibition/Sexual Excitation Scale (SIS/SES), Female Sexual Function Index (FSFI), Female Sexual Distress Scale-Revised (FSDS-R), Body Uneasiness Test (BUT) and Middlesex Hospital Questionnaire (MHQ). A subgroup of patients (n=28) was evaluated at 3-6 months follow-up, using the FSFI and FSDS-R questionnaires. Results: In pre-menopausal women, the SIS1 scale (Sexual inhibition due to the fear of performance failure) was associated with the diagnosis of Hypoactive Sexual Desire Disorder (HSDD), even after adjusting for confounders (p=0.047), whereas in post-menopausal women, we found an association between HSDD and the SES scale (total sexual excitation) (p=0.039; see also Figure 1). Given these correlations, we developed two cut-off values for the SES and SIS1 scales, according to which a score < 49 on the SES (in postmenopausal women) and a score > 34 on the SIS1 (in premenopausal women) accurately identified patients diagnosed with HSDD. In post-menopausal women, the ROC curve for the SES scale showed an accuracy (AUC) of 0.734 +- 0.107, p=0.037, in identifying HSDD; considering a cut-off value of 49, the sensitivity and specificity for HSDD detection were 85.7% and 66.7%, respectively (Fig. 2). In premenopausal women, the ROC curve for the SIS1 scale showed an AUC of 0.853 +- 0.081, p=0.007, in identifying HSDD; considering a cut-off value of 34, the sensitivity and specificity for HSDD detection were 78.6% and 75.0%, respectively (Fig. 3). At follow-up, the mean change in FSFI total score was not correlated with the SES or SIS2 scales (p=0.214 and p=0.402, respectively), but only with the SIS1 scale (p=0.026). When comparing patients with low excitation (SES scale <49) and high inhibition (SIS1 scale >34) with the rest of the sample, they showed a significantly lower change in FSFI total score (p=0.018). Conclusions: In women consulting for FSD, sexual excitation and inhibition, which may be easily assessed by the SIS/SES questionnaire, emerge as key aspects in both the diagnostic evaluation and planning of therapeutic outcomes, in the perspective of a personalized sexual medicine approach. Disclosure: Work supported by industry: no.